Kesejahteraan Psikologis pada Suami-Istri Penghafal Al-Qur’an - Sodiq, Alwi Mahardhika; Widjanarko, Mochamad (Universitas Al Azhar Indonesia, 2024)
The process of memorizing the Koran requires many strategies and challenges. It is certainly not easy for husband and wife couples who have domestic duties to memorize the Koran. The research on the psychological well-being of husbands and wives who memorize the Koran was conducted in order to understand the dynamics they face in terms of psychological well-being. This research used a qualitative method with a phenomenological approach and applies instruments through observation and interviews, both directly and indirectly. The subjects in this study consisted of 2 husband and wife couples who lived in Kudus Regency. Subjects were selected through snowball sampling. The results of this study showed that husband and wife memorized the Koran to give glory to their parents and to implement their knowledge in daily life and pursue happiness in the afterlife. Other results included other psychological functions which are assessed, that are the desire to continue to develop into a better person, a harmonious family, mutual acceptance of each partner's strengths and weaknesses, managing daily activities, being yourself, and establishing positive relationships with other people.Keywords - Hafiz Al-Qur’an, Husband and Wife, Psychological Well Being.